Cidadania: a educação em direitos a emancipação política do homem - Costa, Valquíria Ortiz Tavares (2016)
This work is focused on the role that human rights education plays in building citizenship. Education on Human Rights is currently promoted worldwide, being constantly stimulated and accompanied by the UN itself through its Global Education Program in Human Rights adopted by several countries, among them Brazil. Human rights education aims to instruct the individual in civil, social and political rights in a participatory methodology, which intertwines with social reality, seeking to impart the necessary skills so that the person promote, defend and apply human rights in their everyday life. But human rights education also promotes political education, not allowing political rights to be reduced to simple electoral rituals, thus stimulating the creation of a critical conscience, so that people awake to their potential contribution and transformation of society. The individual then comes to understand that the political decisions define from the most ordinary situations of his life to the guidelines to be adopted by their country, thus changing his/her posture to act actively and consciously in the issues that relate to society, exercising their active citizenship for the common good. In the words of Hannah Arendt, citizenship is the quintessence of freedom, the apex of the possibilities of the acting individual, representing the moment when the citizen assumes its role in the modification and improvement of society. Therefore, education on Human Rights is a sine qua non condition for the exercise of active citizenship